2005
DOI: 10.1063/1.1858532
|View full text |Cite
|
Sign up to set email alerts
|

The influence of turbulence on a columnar vortex

Abstract: The interaction between a columnar vortex and external turbulence is investigated numerically. A Lamb–Oseen vortex is immersed in an initially isotropic homogeneous turbulence field, which itself is produced numerically by a direct numerical simulation of decaying turbulence. The formation of inhomogeneous fine turbulent eddies around the columnar vortex and the vortex-core deformations are studied in detail by visualizing the flow field. The initially random turbulent eddies (worms) are wrapped around the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…This scenario gives a theoretical counterpart to the observation of the recurrent development of vortex rings at the periphery of vortices when submerged in an ambient turbulence (Melander & Hussain 1993;Risso et al 1997;Takahashi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This scenario gives a theoretical counterpart to the observation of the recurrent development of vortex rings at the periphery of vortices when submerged in an ambient turbulence (Melander & Hussain 1993;Risso et al 1997;Takahashi et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…, saturation). In the case of a transient forcing induced by an initially homogeneous isotropic turbulence, Takahashi et al (2005) performed such analysis. The departure from the linear regime happens when the bending wave growing in the core reaches a finite amplitude.…”
Section: Validity Of the Linear Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, the interaction of the sustained vortex and the worms is shown to induce disturbances in the larger vortex core flow that can affect its dynamics. Given the vorticity arrangement shown in Figure 5, it seems plausible to hypothesize that vortex-vortex interactions analogous to those shown by Takahashi et al [49] may occur between tornadoes and surrounding HVs.…”
Section: D Vorticity Structure and Visual Observationsmentioning
confidence: 56%
“…In both observed and simulated tornadoes, the HVs revolve counter-clockwise in the tornadic outer wind field and tend to align azimuthally around (but outside) the tornado core, thus, forming ring-like structures encircling the tornado. Although in a different context, this behavior bears remarkable resemblance to the process by which elongated vortices in isotropic homogeneous turbulence, the so-called "worms" (e.g., [48]), interact with a large, sustained columnar vortex in the DVRs of Takahashi et al [49]. In their study, the interaction of the sustained vortex and the worms is shown to induce disturbances in the larger vortex core flow that can affect its dynamics.…”
Section: D Vorticity Structure and Visual Observationsmentioning
confidence: 85%